PENERJEMAHAN ‘KANDOU’ DALAM KOMIK KIMETSU NO YAIBA VOL 1-3 KARYA KOYOHARU GOTOUGE - Lindayanti, Cucu; Aibonotika, Arza; Charlina, Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study discusses the translation 'kandou' in the comic Kimetsu no Yaiba. The method is descriptive qualitative. The purpose of this study is to discuss form, function and meaning, using semantic translation methods and translation procedures based on Newmark's theory. The results indicated that there are forms maa, ou, oo, e, e', hora, nanda, ara, are, aa, a', waa, kya, and gya. Morphologically, the equivalent forms found there are two forms, namely lexical and grammatical. The lexical form is found in the equivalent of ‘apa’ and the grammatical form is found in the equivalent of ‘wah’, ‘oh’, ‘eh’, ‘tuhkan’, ‘apa ini’, ‘apa-apaan’, ‘apa itu’, ‘kok’, ‘waa’, ‘kya’ and ‘gya’ which shows the function and meaning of feeling surprised, amazed, doubtful, convinced, impressed, suspicious, asking for attention, showing something, asking for meaning, angry, sad, afraid and sick.Key Words: Translation, Kandou, Comic.